Wild and Radioactive Scenery: Nuclearized Landscapes of the Western United States - Genay, Lucie (Intermédialités / Intermediality, 2025)
The West of the United States is world-renowned for its breathtaking scenery and legendary wilderness immortalized through art and literature, conservationist efforts, and tourism. During World War II and the Cold War, the western deserts that had already captured the imagination of travelers, artists, and tourists alike also became major assets in building the US nuclear military industrial complex. A novel, anthropogenic form of landscape was then invented in the region, which acquired a new identity as the “atomic West” and, in turn, led to the emergence of new kinds of tourism and artistic representations of nuclear spaces. Based on a selection of sites, this article critically studies the crossroads between radioactivity and wilderness in the western United States. It asks how western landscapes and desertscapes were nuclearized and what were some of the cultural, environmental, political, and economic implications of this process.